Pengaruh Mengkonsumsi Buah Nanas (Ananas comosus L.merr) dan Buah Pir (Pyrus bretschneideri) terhadap Jumlah Koloni Streptococcus sp. dalam Saliva Anak Usia 10 â 12 Tahun - Marsela, Sendi; Probosari, Niken; Setyorini, Dyah (Fakultas Kedokteran Gigi Universitas Jember, 2015)
Pineapple (Ananas comosus L.merr) and pear (Pyrus bretschneideri) is a fruit that we often encounter in every season and is usually fresh fruit preference. Pineapple contains chlorine, iodine and phenol, while pear contains catechins that are both bactericidal against bacteria that cause caries. This study aimed to determine the effect of eating pineapple and pears, as well as the difference between eating pineapple and pear against colony of Streptococcus sp. in saliva children aged 10-12 years. The results showed the effect of consuming pineapple and pear on the number of colonies of Streptococcus sp. in saliva children aged 10-12 years, and there are significant differences between before and after eating pineapple and pear.